Written Essay Assessment of Philosophical Reasoning in Game-Based Science Teacher Education: Ontological, Epistemological, and Axiological Profiles of Pre-Service Teachers - Rifda Nur Hikmahwati Arif; Banu Kisworo; Yulianti Yusal (BIOCHEPHY: Journal of Science Education, 2026)
Philosophy of Science is a key component of science teacher education because it helps prospective teachers understand the nature of scientific knowledge, its justification, and its educational value. This descriptive qualitative study analyzed essay responses from 78 pre-service science teachers at Makassar State University who participated in a multiplatform game-based Philosophy of Science course. Four essay questions assessed understanding of ontology, epistemology, axiology, and the integration of these three dimensions within junior secondary science education. Data were examined through qualitative content analysis supported by codebook development, repeated reading, peer review, negative-case analysis, and descriptive quantification. Results indicated strong understanding of ontological concepts (95.0% valid responses) and axiological reasoning (96.3%), while epistemological understanding was less developed (59.6%). Integrating the three philosophical dimensions proved most challenging, with only 53.8% valid responses and 40.5% demonstrating complete synthesis. Students primarily recommended debate-based games (31.3%), reflecting an emphasis on critical thinking. These findings provide a framework for assessing philosophical reasoning through essays in game-based science teacher education.